Acknowledgment of Reviewers 2023 (Neurotrauma Reports, 2024)
Critical evaluations of articles by expert reviewers make a vital contribution to ensuring the high quality of a journal's content. The editorial leadership of Neurotrauma Reports is very grateful for the support of the highly qualified peer reviewers who have dedicated their time and effort to reviewing our articles. We would like to show our appreciation by thanking the following individuals for their assistance with the review of articles for the journal in 2023.